An internal charge transfer-dependent solvent effect in V-shaped azacyanines. Issue 48 (20th October 2015) - Tasior, Mariusz; Bald, Ilko; Deperasińska, Irena; Cywiński, Piotr J.; Gryko, Daniel T.
Abstract : Intramolecular charge transfer dictates linear and non-linear optical properties of D–π-A + –π-D compounds. Abstract : New V-shaped non-centrosymmetric dyes, possessing a strongly electron-deficient azacyanine core, have been synthesized based on a straightforward two-step approach. The key step in this synthesis involves palladium-catalysed cross-coupling of dibromo- N, N ′-methylene-2, 2′-azapyridinocyanines with arylacetylenes. The resulting strongly polarized π-expanded heterocycles exhibit green to orange fluorescence and they strongly respond to changes in solvent polarity. We demonstrate that differently electron-donating peripheral groups have a significant influence on the internal charge transfer, hence on the solvent effect and fluorescence quantum yield. TD-DFT calculations confirm that, in contrast to the previously studied bis(styryl)azacyanines, the proximity of S1 and T2 states calculated for compounds bearing two 4- N, N -dimethylaminophenylethynyl moieties establishes good conditions for efficient intersystem crossing and is responsible for its low fluorescence quantum yield. Non-linear properties have also been determined for new azacyanines and the results show that depending on peripheral groups, the synthesized dyes exhibit small to large two-photon absorption cross sections reaching 4000 GM.